Carboniferous and Permian beds from the northern Julian Alps - Ramovš, Anton; Kochansky-Devidé, Vanda (Geologija, 1979)
Paleontologic evidence is given of Upper Carboniferous beds of the Gzhelian stage, and Lower Permian beds of the Sakmarian (Zellia bearing Pseudoschwagerina limestone) and Artinskian (Trogkofel Beds) stages from the northern Julian Alps. Middle Permian formation of the Val Gardena facies could not be recognized. The Upper Permian dolomite is indicated by its stratigraphic position and lithological particularities.